2009
DOI: 10.1002/cncr.24364
|View full text |Cite
|
Sign up to set email alerts
|

Novel chemotherapy approaches for cervical cancer

Abstract: Cancer of the cervix is the second most common malignancy among women worldwide. The last 20 years have lead to numerous advances in the medical management of locally advanced cervical cancer, including preventive vaccination, chemoradiation, and neoadjuvant chemotherapy. The treatment of metastatic disease is palliative at best. Platinum‐based chemotherapy remains the standard of care for inoperable patients who have recurrent disease. However, because most patients initially receive concomitant platinum‐base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 121 publications
1
52
0
Order By: Relevance
“…Nevertheless, effective treatment options for cervical cancer patients are limited. The current approach to treating cervical cancer includes surgery, radiation treatment, and cytotoxic chemotherapy [2]. Identification of the molecular mechanisms underlying novel targeted therapeutic strategies is therefore an important objective for improved treatment of cervical cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, effective treatment options for cervical cancer patients are limited. The current approach to treating cervical cancer includes surgery, radiation treatment, and cytotoxic chemotherapy [2]. Identification of the molecular mechanisms underlying novel targeted therapeutic strategies is therefore an important objective for improved treatment of cervical cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…bevacizumab [29,30], pazopanib [31], or cetuximab [32]), may enhance outcome, there is the potential that unique toxicities may be observed [7], delaying or preventing the delivery of radiation, the single most important component of this strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Despite several decades of intensive research, including the conduct of numerous phase 3 randomized trials, the impact of chemotherapy on the natural history of advanced cervix cancer is appreciated to be (at best) quite modest [1,2,3,4,5,6,7]. …”
Section: The Role Of Chemotherapy Without Concurrent Radiation In Thementioning
confidence: 99%
“…The rationale of giving neoadjuvant chemotherapy before radiation therapy included reducing tumor volume and radio-sensitizing tumors by decreasing the hypoxic cell fraction in large tumors (Movva et al, 2009). However, several randomized trials of such treatment revealed no survival advantage compared with radiation therapy alone (Chiara et al, 1994;Herod et al, 2000;Lacava et al, 1997;Leborgne et al, 1997;Sundfor et al, 1996;Souhami et al, 1991;Symonds, 2000;Tattersall et al, 1992;Tattersall et al, 1995).…”
Section: Neoadjuvant Chemotherapy Before Radiation Therapymentioning
confidence: 99%